The social support network in the care of rare disease and family protagonism (Research, Society and Development, 2020)
Objective: To understand the construction of the social support network for the care of a young person with a rare disease. Methodology: A study with a qualitative approach, such as a case study, carried out with the family of a young man with Epidermolysis Bullosa who lived in the metropolitan region of the Vale do Rio Cuiabá in Mato Grosso, Brazil. Data were collected in three meetings between October 2017 and August 2018 through in-depth interviews and observation. In the analysis the narratives were brought together in different thematic groups identified by the assigned meaning. Results: The family care undertaken underwent complex moments without regular monitoring by health services and professionals, in which the social support network built by the family was essential in coping with the adversities imposed by the disease. Final considerations: The family built a powerful social support network independently with the media, the school and social media, independently and without the assistance of health professionals and services.